Project Activity With The Application Of Information And Communication Technologies - Rimma Massyrova, Victoria Savelyeva, (Opción, 2019)
An article is considered the method of application of the information – communication technologies in the project activity of students, in particular, at lectures, practical studies and IWST (independent work of the student under the guidance of teacher). As a result, the project activity not only activates the student work, but also the teacher. In conclusion, process of system modernization of the education system in itself assumes overcoming the essential elements of old regime, the development of new ideas and, naturally, formation of other mechanisms and methods of the organization of project activity.